2017
DOI: 10.1002/2017jd026707
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of thin cloud detection by applying bidirectional reflectance distribution function model‐based background surface reflectance using Geostationary Ocean Color Imager (GOCI): A case study for South Korea

Abstract: In this study, a new assessment of thin cloud detection with the application of bidirectional reflectance distribution function (BRDF) model‐based background surface reflectance was undertaken by interpreting surface spectra characterized using the Geostationary Ocean Color Imager (GOCI) over a land surface area. Unlike cloud detection over the ocean, the detection of cloud over land surfaces is difficult due to the complicated surface scattering characteristics, which vary among land surface types. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…GOCI provides hourly observations from 00 UTC to 07 UTC, with a spatial resolution of 500 m, which exceeds those of other geostationary satellites observing Northeast Asia, such as the Advanced Meteorological Imager (AMI) and Advanced Himawari Imager [40]. Owing to its advantage of high spatial and temporal resolutions, GOCI has been widely used for land surface, atmosphere, and ocean monitoring [47,48]. In this study, we used GOCI Level 1B (L1B) and GOCI AOD products for atmospheric correction.…”
Section: Satellite Datamentioning
confidence: 99%
See 1 more Smart Citation
“…GOCI provides hourly observations from 00 UTC to 07 UTC, with a spatial resolution of 500 m, which exceeds those of other geostationary satellites observing Northeast Asia, such as the Advanced Meteorological Imager (AMI) and Advanced Himawari Imager [40]. Owing to its advantage of high spatial and temporal resolutions, GOCI has been widely used for land surface, atmosphere, and ocean monitoring [47,48]. In this study, we used GOCI Level 1B (L1B) and GOCI AOD products for atmospheric correction.…”
Section: Satellite Datamentioning
confidence: 99%
“…Son and Kim [46] conducted a feasibility study to produce a land cover map using principal component analysis, K-means clustering, and GOCI NDVI via BRDF modeling. Yeom et al [47] and Kim et al [48] have suggested novel cloud masking methods using BRDF-based background surface reflectance and Top-Of-Atmosphere (TOA) reflectance of GOCI. The abovementioned studies estimated LSR using absolute atmospheric correction.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mapped location of the clouds detected depends, in part, on the VZA, parallax shifts can also complicate comparing the location of clouds between sensors with different VZA (Zakšek et al, 2013). However, it is possible to correct for parallax shifts with knowledge of VZA and feature (cloud or surface) altitude (Kim et al, 2017;Yeom et al, 2020).…”
Section: Parallaxmentioning
confidence: 99%
“…Side scattering into the lidar's field of view from adjacent objects provides negligible enhancement as compared with the active return from the target. Therefore, a lidar can help to validate imager cloud masks, as demonstrated by the many studies that have used lidar data from CALIPSO to validate cloud identification schemes from different imagers (e.g., Hutchison et al, ; Kim et al, ; Kopp et al, ; Marquis et al, ; Wang et al, ).…”
Section: Analysis Of Emas Aerosol Datamentioning
confidence: 99%